Meningkatkan Penjualan Produk Melalui Pemanfaatan Digital Marketing pada Kerajinan Tenun Sutera - Ridfan Rifadly Abadi; Rahmat Riwayat Abadi; Annisa Paramaswary Aslam; Khaidir Syahrul; Andi Dewi Angreyani (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Digital development in urban and rural areas is developing unevenly. The development of technology and information tends to still be centered in urban areas. This then makes it difficult for rural communities to compete in increasing their product sales because of limited access to technological tools and information. In addition, people in rural areas still use traditional marketing methods in marketing their products. Through the use of digital marketing, it is hoped that people will be able to increase their sales through this method. The use of digital marketing media as a promotional medium will allow business actors to have a wider reach in finding new customers, so that it is the key to increasing product sales and strengthening their presence in an increasingly competitive market. Based on these conditions, efforts need to be made in utilizing digital marketing to increase sales so that they can generate more sales and be widely known to the public. The initial step taken by the community service team was to provide socialization to the community regarding training on the use of digital marketing that would be applied to the business group.